Implementing sustainable development integrated assessment and participatory decision-making processes - Abaza, Hussein; Baranzini, Andrea; United Nations Environment Programme; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar Pub., 2002)
Decision-makers increasingly seek to design environmental and development policies that will support sustainable development. Thus, practical tools to help formulate sustainable development policies and clear methods to assess their acceptability and effectiveness are urgently needed. This book contributes to meeting these needs by presenting both analytical and empirical aspects of decision-making processes.
pt. 1. Methodological issues towards integrative analysis -- pt. 2. Participatory frameworks -- pt. 3. Perspectives in ecological economic modelling.
"Published for and in behalf of UNEP."
Includes bibliographical references and index.
Keywords: Sustainable development; Economic development -- Environmental aspects; Electronic books